Clinical and Electrophysiological Correlates of Incessant Ivabradine-Sensitive Atrial Tachycardia. (August 2019) - Banavalikar, Bharatraj; Shenthar, Jayaprakash; Padmanabhan, Deepak; Valappil, Sanjai Pattu; Singha, Sinam Inaoton; Kottayan, Anju; Ghadei, Milan; Ali, Muzaffar
Abstract : Background: Incessant focal atrial tachycardia (FAT), if untreated, can lead to ventricular dysfunction and heart failure (tachycardia-induced cardiomyopathy). Drug therapy of FAT is often difficult and ineffective. The efficacy of ivabradine has not been systematically evaluated in the treatment of FAT. Methods: The study group consisted of patients with incessant FAT (lasting >24 hours) and structurally normal hearts. Patients with ventricular dysfunction as a consequence of FAT were not excluded. All antiarrhythmic drugs were discontinued at least 5 half-lives before the initiation of ivabradine. Oral ivabradine (adults, 10 mg twice 12 hours apart; pediatric patients: 0.28 mg/kg in 2 divided doses) was initiated in the intensive care unit under continuous electrocardiographic monitoring. A positive response was defined as the termination of tachycardia with the restoration of sinus rhythm or suppression of the tachycardia to <100 beats per minute without termination within 12 hours of initiating ivabradine. Results: Twenty-eight patients (mean age, 34.6±21.5 years; women, 60.7%) were included in the study. The most common symptom was palpitation (85.7%) followed by shortness of breath (25%). The mean atrial rate during tachycardia was 170±21 beats per minute, and the mean left ventricular ejection fraction was 54.7±14.3%. Overall, 18 (64.3%) patients responded within 6 hours of the first dose of ivabradine. Thirteen of 18 ivabradine responders subsequently underwent successful catheter ablation. FAT originating in the atrial appendages was a predictor of ivabradine response compared with those arising from other atrial sites ( P =0.046). Conclusions: Ivabradine-sensitive atrial tachycardia constitutes 64% of incessant FAT in patients without structural heart disease. Incessant FAT originating in the atrial appendages is more likely to respond to ivabradine than that arising from other atrial sites. Our findings implicate the funny current in the pathogenesis of FAT.